196 Sleeping Through a Pandemic: Sleep Health in Adults Around the World During the COVID-19 Lockdown. (3rd May 2021) - Yuksel, Dilara; McKee, Grace; Perrin, Paul; Alzueta, Elisabet; Caffarra, Sendy; Ramos-Usuga, Daniela; Arango-Lasprilla, Juan-Carlos; Baker, Fiona
Abstract: Introduction: The novel COVID-19 disease rapidly escalated into a global pandemic affecting people around the world. While communities imposed mitigation measures to stop the spread of the disease, the mass (home) confinement in addition to the uncertainty of the pandemic led to drastic changes in all aspects of life, including sleep. Sleep health is strongly linked with mental and overall health and could play a protective role against the development of mental distress during the pandemic. Here, we investigated sleep health in a global multicultural sample of adults during the COVID-19 pandemic. Methods: We surveyed 6, 882 adults (18-94 years) across 59 countries about their sleep health (RU-SATED scale), sleep behaviors, demographics, pandemic-related factors, and mood between late April and early May 2020. A hierarchical stepwise multiple linear regression was performed to investigate correlates of sleep health. Results: Compared with pre-pandemic times, more than one third of the sample reported an increase in sleep disturbances, and more than half of the sample shifted their sleep schedule towards later bed- and wake-up times. Better sleep health was associated with being partnered, older age and living in a higher-income country (p<.001). Poorer sleep health was associated with a stricter level of quarantine, and other pandemic-related factors including being laid off from job, financial strain, or difficulties with transitioning to working from home (R2=.116, p<.001). Domestic conflict emerged as the strongest correlate of poorer sleep health in the regression model. Greater depression and anxiety symptoms were associated with a poorer sleep health (p<.001). In a global comparison, Latin Americans reported the lowest sleep health scores. Conclusion: Our findings highlight how sleep behavior has changed during the international quarantine- and isolation measurements and show the association between pandemic-related factors and poor sleep health, which, in turn, is closely linked with poorer mental health. These results emphasize the importance of maintaining good sleep health during the pandemic, since poorer sleep health may trigger or exacerbate mental disorders. Maintenance of good sleep health should be incorporated into public health messages aimed at helping people maintain optimal mental and physical health during major stressful life events like the COVID-19 pandemic. Support (if any):